The Diagnostic Value of 18F-FDG PET/CT in Association with Serum Tumor Marker Assays in Breast Cancer Recurrence and Metastasis. (24th March 2015) - Dong, Ying; Hou, Haifeng; Wang, Chunyan; Li, Jing; Yao, Qiong; Amer, Said; Tian, Mei
Abstract : Background . After initial treatment of breast cancer (BC), monitoring locoregional recurrence and distant metastases is a great clinical challenge. Objective . To evaluate the efficacy of PET/CT in association with serum tumor makers in BC follow-up. Methods . Twenty-six women with a history of modified radical mastectomy were evaluated by 18 F-FDG PET/CT. The results of PET/CT were compared with those of conventional imaging techniques (CITs) (including mammography, chest radiography, CT, MRI, ultrasound, and bone scintigraphy). Serum tumor markers of CEA, CA 125, and CA 15-3 in the BC patients were also analyzed in association with the results of PET/CT. Results . Compared with CITs, PET/CT was more sensitive to detect the malignant foci and had better patient-based sensitivity and specificity. The mean CA 15-3 serum level was significantly higher in the confirmed positive patients of PET/CT results than in the confirmed negative ones, while there were no significant differences in the serum levels of CEA and CA 125 of both groups. Conclusion . PET/CT is a highly efficient tool for BC follow-up compared with CITs. The high serum levels of CA 15-3 in confirmed positive PET/CT patients indicated the clinical value of CA 15-3 in BC follow-up.